Resilience of Vocational High School Students After Being Detained by Authorities During the 2025 Solo Demonstrations (Jurnal Wahana Konseling, 2026)
This study aims to describe the resilience of vocational high school students after being detained by authorities during a demonstration in Solo. A qualitative case study approach was employed to explore the lived experiences of two male students from SMK N 5 Surakarta, identified as KCP and MR. Data were collected through semi-structured interviews, observation, and documentation, with additional confirmation from the school counselor. The data were analyzed using Grotberg’s resilience framework, which includes three aspects: I Have, I Am, and I Can. The findings show that both participants developed resilience through different sources and processes. KCP’s resilience was strongly supported by family, particularly his mother, who provided emotional, moral, and religious encouragement. This support helped him develop responsibility, self-acceptance, and motivation to change. In contrast, MR relied more on peer support due to limited family support. His friends provided emotional encouragement and practical assistance in facing the consequences of the incident. Both participants demonstrated responsibility and the ability to endure social stigma, although KCP showed stronger internal change and more adaptive problem-solving. This study concludes that adolescent resilience is dynamic, contextual, and shaped by the interaction of social support, internal strength, and coping ability.